VASCULAR SURGERY AND MYOCARDIAL INJURY AFTER NONCARDIAC SURGERY (MINS): LITERATURE REVIEW - Nóbrega, Leandro (2021)
INTRODUCTION: After noncardiac surgery, cardiac complications are common. Recently there is one that has gained notoriety as risk factor for cardiovascular morbidity and mortality, myocardial injury after noncardiac surgery (MINS). It has an estimated incidence of 8% and is associated with an increased risk of major adverse cardiovascular events (MACE). Thus, the aim of this paper is to review the available literature regarding MINS in Vascular Surgery. METHODS: A Medline search was performed in order to identify articles focused on MINS and its pathophysiology and effect on outcomes in Vascular Surgery. Additional articles of scientific interest for the purpose of this non-systematic review were included by cross-referencing. RESULTS: The incidence of MINS in Vascular Surgery is of at least 15%, higher than in other surgical specialties. As in other areas, MINS has been identified as a risk factor for cardiovascular morbidity and mortality in patients submitted to a vascular surgery. Meanwhile, troponin measurement in the post-operative period is only recommended in high risk patients. Despite the lack of consensus regarding protective factors, dabigatran and statins have showed potential as treatment after the diagnosis of MINS. CONCLUSION: The available evidence identifies MINS as a factor that carries significant worse outcomes in patients that underwent a vascular surgery, although it remains a largely unexplored area.